Radiocesium fate and transport in the soil-water environment in the proximity of the Fukushima Dai-Ichi Nuclear Power Plant - Udy, Cameron, author; Johnson, Thomas, advisor; Sudowe, Ralf, advisor; Borch, Thomas, committee member (Colorado State University. Libraries, 2020)
The objective of this research was to examine the dynamics of Cs-134 and Cs-137 in the aquatic ecosystems of the contaminated areas adjacent to the Fukushima Dai-ichi Nuclear Power Plant (FDNPP). Samples of water, suspended and bottom sediments from rivers, ponds, and a reservoir were collected. Three rivers (Niida, Abukuma, and Maeda), four ponds (Inkyozaka, Suzuuchi, and Funasawa 1& 2), and Sakashita Reservoir located in the Fukushima contaminated area were the focus of the study. Bottom sediment cores were taken from the Sakashita reservoir to analyze vertical distribution of radiocesium (r-Cs). Water samples were collected and filtered using an in-situ filtration system in the field or by using a laboratory filtration system. Dissolved Cs-134 and Cs-137 were removed from water using one of two different sorbents, a cartridge with non-woven cloth impregnated with potassium zinc ferrocyanide or a column filled with granulated cellulose impregnated with Iron Ferrocyanide. Activity concentrations of Cs-134 and Cs-137 were measured via gamma-spectrometry on a high purity Germanium detector, and concentrations of major cations affecting r-Cs behavior were measured via Ion Chromatography and Inductively Coupled Plasma Mass Spectrometry (ICP/MS). R-Cs was concentrated in the sediment in all but two of the river samples. Suzuuchi pond r-Cs was primarily concentrated in the sediment in both samples, but in the other three ponds r-Cs switched between being primarily concentrated in suspended sediment in July from being primarily dissolved in solution during June. Sakashita reservoir r-Cs was primarily dissolved in solution. Mean river Kd values (L/g) were five to ten times higher than the mean values from the ponds and reservoir. River Kd variance was also much higher due to three river sample points having Kd values over 1000 while the rest were below 500.
Keywords: Fukushima; radioecology; radiocesium; distribution coefficient